Exploring the Use of Metafunctions in Ed Sheeran’s “Photograph” Through Halliday’s Systemic Functional Linguistics - Fida Aulianisa; Naela Syafiatuz Zahro; Zahrotul Khafida; Aditya Dina Muhajiroh; Fasah Khairunicha (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
Music is one of the most powerful means of emotional expression, allowing people to convey feelings that words alone often cannot capture. This study analyses Ed Sheeran’s song “Photograph” using Halliday’s Systemic Functional Linguistics (SFL) framework to explore how meaning and emotion are constructed through the three metafunctions: ideational, interpersonal, and textual. The ideational metafunction reveals how Sheeran represents love, memory, and emotional experience; the interpersonal metafunction shows how linguistic choices build intimacy and emotional connection with listeners; and the textual metafunction demonstrates how cohesion and coherence organize the song’s narrative. By combining these three metafunctions, the study illustrates how Sheeran’s lyrical style reflects human emotion in a simple yet profound way. The findings demonstrate that “Photograph” not only portrays personal memories and affection but also represents how language functions as a medium for expressing universal human emotions through music.